Subordinate Resolution ‐‐ An Empirical Analysis of European Union Subsidiary Banks. (4th February 2019) - Conlon, Thomas; Cotter, John
Abstract: To help curtail future sovereign exposures to banking losses, the European Union (EU) introduced the Bank Resolution and Recovery Directive, which mandates bail‐in of creditors in the event of significant bank losses. In this article, we examine the impact of resolution on subsidiary banks, notable in terms of their substantial role throughout the EU. Significant differences in risk and funding characteristics are apparent between domestic and cross‐border European bank subsidiaries. Subsidiary banks are found to possess a larger proportion of loss absorbing capacity than underlying parent banks. Results indicate the suitability of single point of entry resolution in the case of domestic subsidiaries and multiple points of entry resolution for cross‐border subsidiaries. Our findings highlight a worrying decline in loss absorbing capacity in European banks more generally since 2006, pointing to a necessary future focus on broad capital thresholds to ensure the success of the resolution model.